The Principle of Balance In International Business Contract Law (In Anticipation Of The Free Trade Era) - Cindawati, Cindawati (Indonesian Journal of International Law, 2012)
The balance principle contains the ideal of reaching a balance. This includes the balance in a business contract or agreement where respective individual interests are guaranteed by an objective law, specifically in the law of business contracts. This principle regulates parties involved in international business contracts, such as the United Nations Convention on Contracts for the International Sale of Goods 1980, and in the founding of the World Trade Organization (WTO). In the future, the balance principle will be complementary to the law of international business contracts, while arbitration will be the medium to resolve international civil lawsuits. This article found that the application of the balance principle in the law of international business contracts refers to the principle of efficiency in economics and trade in a competitive international business community. Thus, every business person will guard their business reputation and will consequently abide by what has been agreed upon in international business contracts so as to maintain harmony and balance.